2020
DOI: 10.1111/jgh.15148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic closure on adverse events after colorectal endoscopic submucosal dissection: A meta‐analysis

Abstract: Background and Aim Endoscopic submucosal dissection (ESD) has a high en bloc resection rate and is widely performed for large colorectal lesions. However, colorectal ESD is associated with a high frequency of adverse events (AEs), and the efficacy of prophylactic endoscopic closure after ESD for preventing AEs is still controversial. This meta‐analysis was conducted to assess the efficacy of closure on AEs following colorectal ESD. Methods We searched PubMed, Embase, and the Cochrane Library for eligible studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…According to literature, postoperative bleeding and perforation occur in 1.5%-11.9% [ 19 ] and 1.4%-10.4% [ 20 ] of patients, respectively, after colorectal ESD. In our study, the postoperative bleeding rate and perforation rate were both 2.9% in ORB-ESD patients, versus 4.4% and 2.2%, respectively, in conventional ESD patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, postoperative bleeding and perforation occur in 1.5%-11.9% [ 19 ] and 1.4%-10.4% [ 20 ] of patients, respectively, after colorectal ESD. In our study, the postoperative bleeding rate and perforation rate were both 2.9% in ORB-ESD patients, versus 4.4% and 2.2%, respectively, in conventional ESD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, Liu et al 5 performed a meta-analysis and found that prophylactic endoscopic closure following colorectal ESD may help decrease risk of delayed bleeding compared to nonclosure. The meta-analysis did not identify any difference with respect to delayed perforation, but studies remain limited, and more work is needed to evaluate this.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, tension is placed on the suture to minimize the slack between the tacks before deploying the second tack from the push catheter. Using the same mechanism, the third and fourth tacks are then deployed; this is followed by the deployment of a suture cinch to fix the tacks and approximate the margins of the defect (Supplementary Video 1, Figure 1 and Supplementary figure 3) [9]. Suture patterns are described in Supplementary Figure 4.…”
mentioning
confidence: 99%